2016
DOI: 10.1097/tp.0000000000001072
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Differences in the Association Between Hospitalization and Kidney Transplantation Among Waitlisted End-Stage Renal Disease Patients

Abstract: Introduction Even after placement on the deceased donor waitlist, there are racial disparities in access to kidney transplant. The association between hospitalization, a proxy for health while waitlisted, and disparities in kidney transplant has not been investigated. Methods We used United States Renal Data System Medicare-linked data on waitlisted End-Stage Renal Disease (ESRD) patients between 2005 and 2009 with continuous enrollment in Medicare Parts A & B (n=24 581) to examine the association between an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Among waitlisted patients, racial and ethnic minorities were more likely to be hospitalized while waitlisted, decreasing the likelihood of being transplanted [ 188 ]. Once on the inactive list, White patients were more likely than Hispanic patients to resolve issues for inactivity, resulting in reactivation [ 189 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among waitlisted patients, racial and ethnic minorities were more likely to be hospitalized while waitlisted, decreasing the likelihood of being transplanted [ 188 ]. Once on the inactive list, White patients were more likely than Hispanic patients to resolve issues for inactivity, resulting in reactivation [ 189 ].…”
Section: Resultsmentioning
confidence: 99%
“…One retrospective study of over 19,000 liver transplant recipients found that Asian Americans are significantly more likely to be hospitalized at time of wait-listing, 7 indicating a greater likelihood of delayed diagnosis, more advanced disease progression, and decreased chances for transplantation. 8 The need for liver transplants is especially critical for Asian Americans due to an extremely high incidence of hepatitis and resultant hepatic failure. 9 In 2016, nearly 20% of all newly reported cases of chronic hepatitis B in the US occurred in Asian Americans, and the death rate among Asian Americans from hepatitis B was more than triple that of non-Hispanic Black Americans.…”
Section: Asian American Need For Transplantationmentioning
confidence: 99%
“…Hospitalization for waitlisted individuals has documented associations with negative outcomes, including higher mortality while waitlisted 3 , lower likelihood of receiving a transplant 2 and higher likelihood of posttransplant complications 20 . In addition, hospitalizations may increase total medical costs 21 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hospitalization is associated with a lower likelihood of receiving a transplant among waitlisted patients 2,3 . Furthermore, hospitalization may add to increased Medicare costs, making it important to identify potentially modifiable factors.…”
Section: Introductionmentioning
confidence: 99%